Alternative anesthesia of neonatal mice for global rAAV delivery in the brain with non-detectable behavioral interference in adults - Tang, Wannan; Zillmann, Uwe; Sprengel, Rolf (Frontiers in behavioral neuroscience, 2020)
Viral transduced gene expression is the current standard for cell-type specific labelling and cell tacking in experimental neuroscience. To achieve widespread gene expression, a viral delivery method to neonatal rodents was introduced more than two decades ago. Most of those neonatal virus-injection based gene transduction methods in mice have used deep hypothermia for anesthesia, which was reported to be associated with behavioral impairments in respective animals. To explore other options for neonatal viral applications, we applied a combination of Medetomidine, Midazolam and Fentanyl (MMF), each of which can be antagonized by a specific antagonist. Later in their adulthood, drug treated, virus injected mice and naïve mice showed a similar performance in all behavioral tasks tested, including motor coordination tasks, anxiety-related tasks and spatial memory tasks, demonstrating MMF anesthesia could be safely applied to mice for neonatal viral transduction at postnatal day 2.
Gesehen am 28.09.2020